Integrated Metabolomics and Network Pharmacology to Establish the Action Mechanism of Qingrekasen Granule for Treating Nephrotic Syndrome - Duan, Yanfen; Zhang, Dongning; Ye, Yan; Zheng, Sili; Huang, Ping; Zhang, Fengyun; Mo, Guoyan; Huang, Fang; Yin, Qiang; Li, Jingjing; Han, Lintao (Frontiers in Pharmacology, 2021)
Nephrotic syndrome (NS) is a clinical syndrome resulting from abnormal glomerular permeability, mainly manifested edema and proteinuria. Qingrekasen granule (QRKSG), a Chinese Uyghur folk medicine, is a single-flavor preparation made from chicory, widely used in treating dysuria and edema. Chicory, the main component in QRKSG, has been effective in treating edema and protecting the kidneys. However, the active components in QRKSG and its underlying mechanism in the treatment of NS remain unclear. Therefore, the objective of this study was to explore the specific mechanism and composition of QRKSG on an NS rat model using integrated metabolomics and network pharmacology. First, metabolomics was used to explore the relevant metabolic pathways impacted by QRKSG in the treatment of NS and to further explore the possible metabolite targets through network pharmacology. Afterward, a comprehensive network was constructed using the results from the network pharmacology and metabolomics analysis. Finally, the interactions between the active components and targets were predicted by molecular docking, and the differential expression levels of the target protein were verified by Western blotting. Metabolomics results showed that “D-Glutamine and D-glutamate metabolism” and “Alanine, aspartate and glutamate metabolism” were the main metabolic pathways targeted in the treatment of NS in rats. AKT1, BCL2L1, CASP3, and MTOR were the core targets of QRKSG in the treatment of NS. Molecular docking revealed that the core targets have a strong affinity for flavonoids, terpenoids, and phenolic acids. In addition, the expression levels of p-PI3K, p-AKT1, p-mTOR, and CASP3 in the QRKSG group were significantly decreased, while BCL2L1 was increased compared to the model group. The findings in this study identified the underlying mechanism of QRKSG as promoting autophagy and anti-apoptosis through the expressions of AKT1, CASP3, BCL2L1, and mTOR to protect podocytes and maintain renal tubular function.